Junction behavior of n-Si photoanodes protected by thin Ni elucidated from dual working electrode photoelectrochemistry - Laskowski, Forrest A. L.; Nellist, Michael R.; Venkatkarthick, Radhakrishnan; Boettcher, Shannon W. (Energy & environmental science, 2017)
Si is a desirable photoanode material for use in photoelectrochemical water-splitting devices. However, Si self-passivates during the oxygen evolution half reaction and requires a protection layer to maintain high photoanodic efficiency. Thin evaporated metallic Ni layers have been reported to protect Si while also enhancing the kinetics for oxygen evolution. Maximizing performance of these and related protected/catalyzed semiconductors requires a fundamental understanding of the semiconductor|catalyst|solution interface. We use dual-working-electrode (DWE) photoelectrochemistry measurements to directly measure the interface's electronic properties in situ during operation. By controlling the Ni thickness (3, 5, and 20 nm), we confirm that favorable shifts in photocurrent onset are correlated with thinner protection layers. Photoelectrochemical DWE measurements are used to test various prevailing hypotheses for the origin of this behavior. We find evidence that increased photovoltage is due to the development of a spatially inhomogeneous buried junction wherein high barrier regions arise via adventitious SiO 2 growth. Thinner protection layers more readily promote this behavior by facilitating solution permeation to the n-Si|Ni interface. Repeated electrochemical cycling of thicker catalyst layers can achieve similar behavior and improve the photocurrent onset by as much as 300 mV. The results are discussed in the context of the general design principles for metal–insulator–semiconductor protected photoanodes.